2012
DOI: 10.1007/s10344-011-0597-8
|View full text |Cite
|
Sign up to set email alerts
|

Method of releasing and number of animals are determinants for the success of European ground squirrel (Spermophilus citellus) reintroductions

Abstract: Reintroductions are considered an important part of the action plans and recovery strategies of endangered ground squirrel species, but so far little is known about their proper methodology. We collected primary data on 12 European ground squirrel reintroduction projects carried out at 14 localities in the Czech Republic, Slovakia and Poland since 1989. We focused on seven methodological aspects of each reintroduction: selection of release site, method of releasing, date of releasing, origin of released animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…In some cases (i.e., burrowing owls [Mitchell et al, ] and Canadian lynx [Devineau et al, ]), soft‐release methods significantly improve post‐release survival; in other cases (i.e., Tawny owls [Griffiths et al, ] and hare wallabies [Hardman and Moro, ]) soft‐versus hard‐release method has little to no influence on survival of released animals. While there is some evidence that the length of time animals are allowed access to soft‐release conditions may influence survival rates [Hamilton et al, ; Rouco et al, ], evidence is also accumulating that factors such as release cohort size and release‐site habitat quality may be more salient to translocation success [Robinette et al, ; Linklater et al, ; Matějů et al, ; Shier and Swaisgood, ]. In the current example, habitat quality at both our hard‐ and soft‐release sites may have been equivalent, and resulted in the lack of effect of release method and pre‐release weight on post‐release growth.…”
Section: Discussionmentioning
confidence: 77%
“…In some cases (i.e., burrowing owls [Mitchell et al, ] and Canadian lynx [Devineau et al, ]), soft‐release methods significantly improve post‐release survival; in other cases (i.e., Tawny owls [Griffiths et al, ] and hare wallabies [Hardman and Moro, ]) soft‐versus hard‐release method has little to no influence on survival of released animals. While there is some evidence that the length of time animals are allowed access to soft‐release conditions may influence survival rates [Hamilton et al, ; Rouco et al, ], evidence is also accumulating that factors such as release cohort size and release‐site habitat quality may be more salient to translocation success [Robinette et al, ; Linklater et al, ; Matějů et al, ; Shier and Swaisgood, ]. In the current example, habitat quality at both our hard‐ and soft‐release sites may have been equivalent, and resulted in the lack of effect of release method and pre‐release weight on post‐release growth.…”
Section: Discussionmentioning
confidence: 77%
“…Black-tailed prairie dogs (Cynomys ludovicianus) released into sites with existing burrows exhibit reduced dispersal and higher survival than those released into sites without burrows (Truett et al 2001). If natural shelters are not available, implementing a softrelease method by temporarily holding animals at the site prior to release to allow for acclimation, or by providing artificial sheltering structures has improved success for some relocated species (Fischer and Lindenmayer 2000;Truett et al 2001;Matějů et al 2012;Dean et al 2016). Animals translocated by these soft release methods exhibit reduced post-release exploratory movement, higher long-term site fidelity, and increased survival when compared to those translocated using hard releases (Bright and Morris 1994;Van Vuren et al 1997;Mathews et al 2006;Hale et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, an action plan for S. citellus has been developed in the Czech Republic (Matěju˚et al 2010a). Several conservation programs have attempted to reintroduce or translocate the species into suitable habitats without great success (Hulova´and Sedla´ček 2008;Matěju˚et al 2010b), except in Poland, where it is considered as successful (Coroiu et al 2008;Matěju˚et al 2010bMatěju˚et al , 2012. In Moldova, S. citellus is rare in the steppe and meadow ecosystems and has been included in the country's Red Book (Teleuta et al 2004).…”
Section: Conservationmentioning
confidence: 96%
“…In a field experiment, Gedeon et al (2012) found that squirrels preferred angled artificial burrows (about 308), which facilitated digging, and medium-height grass (X ¼ 18 -SE 1.5 cm) with overhead protection by grasses as an important component after a translocation of animals. Matěju˚et al (2012) found that a soft method of releasing (i.e., use of artificial burrows or fences or both) is an essential component of a successful reintroduction.…”
Section: Conservationmentioning
confidence: 99%